A Glucuronic Acid-Producing Endophyte Pseudomonas sp. MCS15 Reduces Cadmium Uptake in Rice by Inhibition of Ethylene Biosynthesis - Qian, Lisheng; Song, Fei; Xia, Jinlin; Wang, Rongfu (Frontiers in Plant Science, 2022)
Dynamic regulation of phytohormone levels is pivotal for plant adaptation to harmful conditions. It is increasingly evidenced that endophytic bacteria can regulate plant hormone levels to help their hosts counteract adverse effects imposed by abiotic and biotic stresses, but the mechanisms underlying the endophyte-induced stress resistance of plants remain largely elusive. In this study, a glucuronic acid-producing endophyte Pseudomonas sp. MCS15 alleviated cadmium (Cd) toxicity in rice plants. Inoculation with MCS15 significantly reduced the content of ethylene and down-regulated the expression of iron uptake-related genes in the Cd-treated roots. Similarly, glucuronic acid treatment also remarkably inhibited root uptake of Cd and reduced the production of ethylene. However, treatment with 1-aminocyclopropyl carboxylic acid (ACC), a precursor of ethylene, almost abolished the MCS15 or glucuronic acid-induced inhibition of Cd accumulation in rice plants. Conversely, treatment with aminoethoxylvinyl glycine (AVG), an inhibitor of ethylene biosynthesis, markedly reduced the Cd accumulation in plants. Taken together, our results revealed that the endophytic bacteria MCS15-secreted glucuronic acid reduced the production of ethylene in rice roots, which contributed to preventing the Cd accumulation.